Desarrollo de Lenguaje Oral y su influencia en el proceso de Aprendizaje en niños de 3 a 5 años de edad de la escuela de Educación Básica “Rafael Cajiao Enríquez” de la parroquia Pastocalle barrio Cuilche Miño del año lectivo 2018-2019 - Toapanta Alomoto, Glenda Marcela (2020)
The research carried out addresses a problem that is related to children from 3 to 5 years of age, who have difficulties when expressing their desires, feelings, concerns, and emotions when interacting with others, for this reason it has been necessary to carry out the This research allows to raise the objectives to improve oral language in the learning process, thus developing a methodological strategy based on a guide to phonoarticulatory exercises. For this research, the quantitative method, deductive method, and also has a critical-purposeful investigation, deductive theoretical framework, dialectical theoretical framework, dialectic method and finally the historical theoretical method. During the research process, the empirical method was taken into account, such as: observation, survey and interview, thus determining the statistical method. Once the research methodology was established, the respective instruments were developed, thus being able to establish the appropriate conclusions and recommendations. The methodological strategy was validated through the criteria of experts and users; The same that has allowed to sustain an acceptance, being a positive help for the application of the strategy, achieving a great impact of change in children from 3 to 5 years of the "Rafael Cajiao Enríquez" basic education school in the parish of Pastocalle Cuilche Miño neighborhood.